Factors associated with dietary patterns (DPS) and nutritional status among pregnant women in AM-HDSS, South Ethiopia - Fikadu, Teshale; Tamiru, Dessalegn; Ademe, Beyene Wondafrash (Frontiers in Nutrition, 2024)
Background Malnutrition during pregnancy increases the risk of chronic illness later in life and adverse birth outcomes in subsequent generations. In this regard, consumption of diets rich in adequate energy, protein, vitamins, and minerals from a variety of foods is essential. Evidence on the status of maternal dietary pattern is very crucial. Hence, the aim of this study was to assess factors associated with dietary patterns and nutritional status of pregnant women in South Ethiopia. Methods A community-based cross-sectional study was conducted among 638 randomly selected pregnant women using a validated, a pre-tested, contextualized food frequency questionnaire using interviewer-administered structured questionnaire by digital open-source toolkit. Principal component factor analysis was employed to determine dietary patterns. Bivariable and multivariable ordinal logistic regression analyses were used to identify factors associated with dietary patterns and nutritional status, using STATA version 16. Result The dietary habits of pregnant women were best explained by three distinct dietary patterns. Urban dwellers (AOR = 2.18; 95% CI: 1.33, 3.59), from high socio-economic status (AOR = 2.43; 95% CI: 1.68, 3.51), from middle socio-economic status (AOR = 1.72; 95% CI: 1.19, 2.48), primigravida mothers (AOR = 1.72; 95% CI: 1.07, 2.78), and multigravida mothers (AOR = 2.08; 95% CI: 1.39, 3.10) were high likelihood to consume the highest tercile of “Cereals-Pulses and Dairy” compared to rural dwellers, from low socio-economic status and grand multigravida, respectively. Attending formal education (AOR = 1.60; 95% CI: 1.02, 2.51), from higher socioeconomic status (AOR = 1.56; 95% CI: 1.02, 2.38), not having food aversion (AOR = 1.98; 95% CI: 1.16, 3.39), and had good dietary knowledge (AOR = 2.16; 95% CI: 1.08, 4.32) were associated with a higher tercile consumption of “Nutrient-Dense” food compared to those without formal education, having food aversion and had poor dietary knowledge, respectively. Not attending formal education (AOR = 2.22; 95% CI: 1.48, 3.36), had decision-making autonomy (AOR = 1.91; 95% CI: 1.26, 2.90), and had good dietary knowledge (AOR = 1.86; 95% CI: 1.13, 3.08) were found to consume the highest tercile of “Leafy local food” compared to their counterpart. Consumption of lower terciles “Nutrient-Dense” food (AOR = 1.63; 95% CI: 1.07, 2.47) and “Leafy local food” (AOR = 2.32; 95% CI: 1.54, 3.51) were found to be factors associated with under nutrition during pregnancy. Conclusion Three distinct dietary patterns were identified. Factors associated with these major dietary patterns included place of residence, socio-economic status, educational level, dietary knowledge, food aversion, number of pregnancies, and maternal decision-making autonomy. Under nutrition among pregnant women was found to be high and associated with the consumption of ‘Nutrient-Dense’ and ‘Leafy local’ foods. Therefore, concerned health authorities should strengthen dietary counseling during pregnancy, provide family planning services, and promote women’s education.